PENGARUH KOMPLEKSITAS AUDIT DAN SKEPTISME PROFESIONAL AUDITOR PADA PENERIMAAN PERILAKU DISFUNGSIONAL AUDIT - Septiani, Ni Made Indri; Sukartha, I Made (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
Professional conduct public accountant one of which is in the form of deviant behavior in the audit avoid commonly called the audit dysfunctional behavior. Audit dysfunctional behavior is any action taken in the implementation of the auditor's audit program that can degrade the quality audit. This study aimed to demonstrate empirically the effect of the complexity of the audit and the auditor's professional skepticism in the audit acceptance of dysfunctional behavior in the public accounting firm in Bali. The samples taken by 62 auditors. Samples were selected by using purposive sampling method, the sampling using specific criteria. The data collection is done by questionnaires. The analysis technique used is the Multiple Linear Regression Analysis. The results showed that the variable complexity of the audit  have positive effect on the acceptance of dysfunctional behavior audit and the auditor's professional skepticism variables have negatively influence the acceptance of dysfunctional audit behavior.
Keywords: acceptance of dysfunctional; audit behavior; the complexity of the audit; the auditor' s professional skepticism